FINANCIAL TECHNOLOGY (FINTECH) REVIEWED ACCORDING TO THE PERSPECTIVE OF FOUR ULEMA OF FIQIH (HANAFI, MALIKI, SYAFI'I AND HAMBALI) - Al-Mu'min, A Khaerul Mu'min (Ekonomi Islam, 2024)
Financial Technology (Fintech) is a digital transaction tool that is developing in today's society. Many companies are developing fintech and using it for practical and easy transactions. Sellers and buyers do not need to meet face to face and can do this at their respective homes. With this convenience, there is a need for sharia rules that regulate fintech law. The aim of this research is to provide an overview of fintech law from a fiqh perspective, so that people can analyze whether to use fintech or use traditional finance. As a result of this research, researchers found elements that exist in fintech in the form of offline or online buying and selling, saving or top-up systems, MLM and borrowing and borrowing. Of all the opinions of the four Ulema of Fiqh, differences were found between the schools of jurisprudence according to their reasons. However, basically fintech is allowed as long as the transactions do not contain gharar and usury.